PERAN GURU PAI DALAM PROSES PENGEMBANGAN MEDIA DAN SUMBER BELAJAR YANG MENDUKUNG PEMBELAJARAN AKTIF DAN KREATIF - Sabiqa Awwalina, Linlin; Nugraha, Mulyawan Safwandy (Dirasa Islamiyya: Journal of Islamic Studies, 2023)
The background of this research is technological advances in the world of education which have changed lifestyles which have implications for thought patterns, learning styles and interactions so that the communication paradigm is not only based on conveying information, but the learning process can create an active and creative atmosphere so that students are involved in the material being taught. taught is achieved in accordance with educational goals. The rise of content circulating online adds to teachers' caution in choosing learning resources, in fact not all PAI teachers are responsive to technological advances. This research uses a qualitative approach with a case study type of research to obtain in-depth information on a problem by collecting data in the form of observations and interviews with PAI teachers from each level, both primary and secondary. Once the data is collected, it is analyzed using data triangulation and relevant materials. The research results show several opportunity and obstacle factors with indicators for developing media and learning resources in the form of relevance of the curriculum to media and learning resources, suitability of materials, creativity and innovation, involvement of students, and availability of creative resources. The conclusion obtained is that technological advances have a positive impact on education which is able to explain abstract things so that it will produce an active and creative learning process.